Persistent Diarrhea: Possible Risk Factors in Indonesia - Sunoto Sunoto (Paediatrica Indonesiana, 1993)
From the management point of view, acute diarrhea in Indonesian children is not a big problem anymore. Persistent diarrhea, although the prevalence is less than 10% of acute diarrhea, hut the case fatality rate is about 5-7 times higher which is account for 30-50% of total diarrhea deaths. There are many factors which may contribute to the etiologies of persistent diarrheas. They are among others the specific agents mainly the invasive bacterias (Galmonella spp, Shigella spp, Campylobacter spp, Enteroinvasive E. coli, etc.), Giardia Lamblia and E. histolytica; malnutrition, malabsorption syndromes, systemic infections mainly measles; and last but not least the missmanagement of acute diarrhea, particularly the abundance use of antibiotics and antidiarrheal agents, the late of giving food to the patients and the too early giving semisolid food in normal young baby less than 4-6 month of age.